Om idræt, sociologi og historie i oplevelsessamfundet - Nagbøl, Søren (Forum for Idræt, 1999)
On sport, sociology and history in a culture of sensation This essay On sport, sociology and history in a culture of sensation deals with the dilemma of sociology and the culture of sensation. Over the past 20 years, everyday life has become increasingly aestheticized to the point where it is no longer dominated by economic but by psycho-physical presence. We find ourselves part of a society in rapid motion, surrounded by changes which have great significance for the development of everyday life. How are we supposed to find our way through this multiplicity of signs, of accidents and events? This is a problem for sociology and its sphere of interest. This theme will be considered here in relation to an introduction to the sociology of figuration and knowledge. References will be made to symbolisation processes, to socialisation and fragmentation in a culture of sensation.